Morphophysiological aspects of ornamental sunflowers cultivated in different growing seasons under semi-arid conditions - Sheila D. P. da Silva; Gracielle P. de Souza; Agnaldo R. de M. Chaves; Marcelle A. da Silva; Rafaela R. de Souza; Márkilla Z. Beckmann-Cavalcante (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Knowledge of how climatic conditions affect plant morphophysiology is essential for understanding how to manage the growth cycles of different crops. The aim of this study was to evaluate the effects of the growing seasons in a semi-arid area on the morphophysiological variables of ornamental sunflower plants. The experiment was carried out in a randomized block design in a split-plot arrangement with four replicates. Six cultivars (‘Bonito de Outono Sortido’, ‘Sol Noturno’, ‘Sol Vermelho’, ‘Jardim Amarelo Alto’, ‘Girassol F1 Sunbright Supreme’ and ‘Girassol F1 Vincents Choice’) were evaluated in the main plots and two different growing seasons (GS) in the subplots (GS1 - warm climate and GS2 - mild climate). Evaluations of gas exchange, chlorophyll indices, and leaf surface area were carried out at the reproductive stage (R5.5). The cultivation of ornamental sunflowers in semi-arid regions was significantly affected by the growing season. Changes in gas exchange variables and the morphophysiology of ornamental sunflower plants in the two growing seasons reflected the high phenotypic plasticity characteristic of this species. The cultivation of ornamental sunflowers under semi-arid conditions in the growing season, when air temperature and solar radiation are high, could be limited due to elevated transpiration rates. Therefore, it is recommended that they are grown mainly during the moderate climatic season in semi-arid regions.